Analysis of competitiveness on the market of milk and dairy products in Romania - Maria Nica (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
The dairy sector is indispensable for the overall development of an economy because it provides a vital link between agriculture and industry. This helps diversify and market agricultural products; increases farmer income; creates markets for food exports, and generates more employment opportunities. The purpose of this paper will be to identify consumers' preferences for these products, the reasons for non-consumers, the wishes of onsumers, the economic and financial situation of the main milk and dairy producers, the competitive dairy market as well as the information revealed by the consumer profile questionnaire sources of information and brands known to consumers. The stage of the milk and dairy market in Romania will be assessed, and then the competitiveness on the milk and dairy market in Romania will be analysed. Competitiveness requires special attention, each company has to compare products, prices, promotion and have competitive advantages constantly. In order to determine competitiveness, marketing researches on consumer preferences for milk and dairy products will be used; at the same time, the economic and financial performance of the main economic agents on this market will be analysed. The end of this study will be concretized by the comparative analysis of consumer preferences and the order of companies offered by their economic performance.
Keywords: Q12; Q13; 330; competitiveness; milk market; economic performance; marketing research